2019
DOI: 10.1007/s40858-019-00289-w
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Golovinomyces orontii using species-specific primers and high-resolution melting analysis

Abstract: This study presents the development of species-specific PCR primers for detection of Golovinomyces orontii, the causal agent of powdery mildew disease on different cucurbit hosts. The species-specific primers CgF2 and CgR2 were designed based on partial ITS and 5.8S rDNA sequences using an isolates collection of powdery mildew and downy mildew pathogens from different sources. After optimization of the PCR conditions, a 233 bp fragment was amplified only from DNA of G. orontii. Limit of detection was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Both the species-specific PCR primer pairs (PcK F&R and PxK F&R) validated under individual PCR assays, as mentioned above, were subjected for validation under duplex PCR assay mode. The specificity of the duplex PCR assay was evaluated against different test microbial isolates as mentioned in Table 2 , including the test microbes used in the Nayak et al ( 2019 ) and genomic DNA obtained from dually infected cucumber ( P. cubensis CsKD11 and P. xanthii CsKP07) leaf samples (Table 4 ) was used as a positive control. The duplex PCR assay showed amplification only in positive samples with two distinctly separated specific bands of ~ 705 bp and ~ 290 bp (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both the species-specific PCR primer pairs (PcK F&R and PxK F&R) validated under individual PCR assays, as mentioned above, were subjected for validation under duplex PCR assay mode. The specificity of the duplex PCR assay was evaluated against different test microbial isolates as mentioned in Table 2 , including the test microbes used in the Nayak et al ( 2019 ) and genomic DNA obtained from dually infected cucumber ( P. cubensis CsKD11 and P. xanthii CsKP07) leaf samples (Table 4 ) was used as a positive control. The duplex PCR assay showed amplification only in positive samples with two distinctly separated specific bands of ~ 705 bp and ~ 290 bp (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The ITS region of the rDNA gene cluster has established as a suitable target for fungal species-specific primers due to their high copy number, sequence variability, and fidelity among pathogen species or subspecies. Several researchers reported that the identification of obligate fungi causing powdery mildew and downy mildew diseases by developing species-specific primers targeted on ITS region of rDNA (Wang et al 2008 ; Pirondi et al 2015 ; Bandamaravuri et al 2015 ; Lee et al 2016 ; Nayak et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations